2009
DOI: 10.1093/annonc/mdn681
|View full text |Cite
|
Sign up to set email alerts
|

EGFR, pMAPK, pAkt and PTEN status by immunohistochemistry: correlation with clinical outcome in HER2-positive metastatic breast cancer patients treated with trastuzumab

Abstract: In HER2-positive metastatic breast cancers, EGFR, pMAPK, pAkt and PTEN status evaluated by IHC was not significantly associated with response to trastuzumab, TTP, OS and CNS metastases incidence. However, HER2 status determined by IHC and/or FISH assays may not be sufficient to predict response to trastuzumab-based therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
37
0
10

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 22 publications
6
37
0
10
Order By: Relevance
“…Oncogenic mutations of PIK3CA and low expression or loss of the phosphatase and tensine homologue gene (PTEN), that antagonizes the action of PIK3CA, have both been described as factors that activate the PI3K/AKT pathway and contribute to trastuzumab resistance in breast tumors [6,7]. Investigation in cell lines and clinical studies have suggested the possible use of the PIK3CA and PTEN status as predictive factors of trastuzumab efficacy in breast cancer [7][8][9][10][11] and in one study PIK3CA mutations were found to be mutually exclusive with PTEN loss [12]. In the present study we analyzed samples from patients with presumed HER2-positive breast tumors that were treated with trastuzumab, after local evaluation for HER2 by IHC.…”
Section: Introductionmentioning
confidence: 99%
“…Oncogenic mutations of PIK3CA and low expression or loss of the phosphatase and tensine homologue gene (PTEN), that antagonizes the action of PIK3CA, have both been described as factors that activate the PI3K/AKT pathway and contribute to trastuzumab resistance in breast tumors [6,7]. Investigation in cell lines and clinical studies have suggested the possible use of the PIK3CA and PTEN status as predictive factors of trastuzumab efficacy in breast cancer [7][8][9][10][11] and in one study PIK3CA mutations were found to be mutually exclusive with PTEN loss [12]. In the present study we analyzed samples from patients with presumed HER2-positive breast tumors that were treated with trastuzumab, after local evaluation for HER2 by IHC.…”
Section: Introductionmentioning
confidence: 99%
“…25 On the other hand, some studies found no correlation between PTEN expression and trastuzumab response or survival in patients with HER2-positive breast cancer. 27,28 These contradictory findings prompted us to further investigate the association between PTEN status and clinical outcomes in a large cohort of patients with MBC who were treated with trastuzumab-based therapy. We tested the hypothesis that a comprehensive assessment of PI3K pathway activation status provides biomarkers that can identify patients who may not benefit from trastuzumab-based therapy.…”
mentioning
confidence: 99%
“…We discovered that patients with HER2-positive tumors with strong PTEN expression had a 100% survival rate. Some authors reported no relationship between PTEN loss in HER2-positive tumors and response to trastuzumab treatment [22,33], overall [33] as well as relapse/metastasis-free survival [32,33]. In other studies shorter survival for individuals with HER2 overexpressing tumors with PTEN loss [22,32] or shorter time to progression [12] was noted.…”
Section: Discussionmentioning
confidence: 99%